Free transportation and the related liability in United Arab Emirates - Kadhum, Mohaimen I.; Kamal H. Hassan (Penerbit Universiti Kebangsaan Malaysia, 2019)
The transport of persons for a fare creates a contract that obliges a transporter to transport passengers to their agreed destinations safely. Where a passenger suffers harm during transportation, the transporter would be assumed to have breached this obligation. Therefore, it would be contractually liable to compensate that passenger, unless intervention by an external cause is proven. This article dwells on a different type of transportation. It examines cases where a passenger is transported without the payment of a fare to the transporter. The article focuses primarily on free transportation, as an example of such contracts, but also examines other cases such as secret transportation, curious transportation, driving school contracts and staying aboard a vehicle after the expiration of a transportation contract. The problem posed to both the law and the courts is whether these types of transportation also create contracts, the breach of which would render transporters contractually liable. This article seeks to determine the type of liability faced by such transporters where passengers are harmed during transportation, or its disruption, including the timeframe for such liability. Based on the analysis of legal opinions, relevant legislation and case law, it can be surmised that, in these cases, the transporter may be subject to either tortious liability or presumed liability rules, and, very rarely, to contractual liability rules.